A Novel Collision Supervision and Avoidance Algorithm for Scalable MAC of Vehicular Networks. Issue 1 (1st January 2021) - Shuai, WANG; Yan, LU; Jie, ZHU; Ping, WANG
Abstract : In order to meet low‐latency and ultrareliable requirements on safety services in vehicular networks, this paper proposes a novel Collision supervision and avoidance (CSA) algorithm for the contention based scalable media access control protocol. The two‐dimensional Markov chain model of adaptive backoff state transition criterion in CSA has been built, which could efficiently match the backoff states of nodes to the dynamic changes of vehicular networks. The scalable transmissions can be achieved through supervised trend and matching backoff mechanisms with three adaptive backoff modes. The packet transmit probabilities for the backoff modes have been derived with the theoretical result of the enhanced throughput. The simulation results show the remarkable scalability performance such as normalized throughput > 0.92, PDR > 86% and delay < 6.5ms even in the high‐density and high‐mobility environment.